Persistence of SARS-CoV-2 Infection in Severely Immunocompromised Patients With Complete Remission B-Cell Lymphoma and Anti-CD20 Monoclonal Antibody Therapy: A Case Report of Two Cases - Martínez-Chinchilla, Carlos; Vazquez-Montero, Lucía; Palazón-Carrión, Natalia; Fernández-Román, Isabel M.; López-Barba, José; de la Cruz-Merino, Luis; Rodríguez-Baño, Jesús; Palacios-Baena, Zaira R. (Frontiers in Immunology, 2022)
Immunosuppressant conditions such as hematological malignancies increase the risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. It has been described in the literature that patients on anti-CD20 maintenance therapies for lymphoid malignancies are susceptible to having recurrent flares together with viral replication or reinfections, although these cases are scarce. These patients are not well represented in randomized controlled trials, and as a consequence, the evidence for the use of certain treatments in this scenario is lacking. We present two cases of patients with B-cell lymphoma on remission and treated with rituximab on maintenance. They developed at least 1 flare of coronavirus disease 2019 (COVID-19) after acute infection and always after receiving rituximab. RT-PCR was positive in the nasopharyngeal swab and also in plasma. Patients were treated during flares with remdesivir, hyperimmune plasma, and corticosteroids. These two cases showed the unresolved problem of COVID-19 in immunosuppressant patients and showed that despite the vast amount of information available on SARS-CoV-2, information in this subgroup of patients is lacking.